From Amino Acids to Nature-Inspired Molecular Scaffolds: Incorporation of Medium-Sized Bridged Heterocycles into a Peptide Backbone - la Venia, Agustina (2014)
Novel molecular scaffolds comprising two to four bridged and fused heterocycles were synthesized from amino acids using seven-membered endocyclic N-acyliminium ions as key intermediates in acid-mediated tandem reactions with internal nucleophiles. This complexity-generating synthesis proceeds with high efficiency and with full stereocontrol of the newly generated stereogenic center. These results have extended the scope of medium-sized cyclic iminium ion chemistry, making it applicable as a regio- and stereoselective synthetic strategy for the generation of complex polycyclic structures. Furthermore, its compatibility with the traditional Merrifield synthesis of peptides on solid supports allowed the incorporation of the previously unexplored conformationally restricted cyclic systems into peptides without a need to independently synthesize the scaffold